2010
DOI: 10.1074/jbc.m110.154427
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of a Novel Cytoskeletal Protein (RsmP) Regulates Rod-shaped Morphology in Corynebacterium glutamicum

Abstract: Corynebacteria grow by wall extension at the cell poles, with DivIVA being an essential protein orchestrating cell elongation and morphogenesis. DivIVA is considered a scaffolding protein able to recruit other proteins and enzymes involved in polar peptidoglycan biosynthesis. Partial depletion of DivIVA induced overexpression of cg3264, a previously uncharacterized gene that encodes a novel coiled coil-rich protein specific for corynebacteria and a few other actinomycetes. By partial depletion and overexpressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 72 publications
0
37
0
Order By: Relevance
“…Such a role for STKs in controlling assemblages of coiled-coil proteins is well known in eukaryotes, a classic example being the disassembly of the nuclear lamina mediated by cyclin-dependent kinases (41). In addition, it was recently reported that the assembly and subcellular localization of the coiled-coil protein RsmP in Corynebacterium glutamicum is affected by phosphorylation (42). However, it cannot be excluded that phosphorylation may also influence other aspects of DivIVA behavior, such as its interaction with other proteins or the membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Such a role for STKs in controlling assemblages of coiled-coil proteins is well known in eukaryotes, a classic example being the disassembly of the nuclear lamina mediated by cyclin-dependent kinases (41). In addition, it was recently reported that the assembly and subcellular localization of the coiled-coil protein RsmP in Corynebacterium glutamicum is affected by phosphorylation (42). However, it cannot be excluded that phosphorylation may also influence other aspects of DivIVA behavior, such as its interaction with other proteins or the membrane.…”
Section: Discussionmentioning
confidence: 99%
“…(B) Domain structure of bacterial CCRPs. The positions of coiled‐coil regions in crescentin, FilP, and RsmP are shown as reported previously [Ausmees et al, ; Fiuza et al, ; Walshaw et al, ]. Coiled‐coil segments in Ccrp59 and Ccrp1143 were determined using the COILS server [Lupas et al, ].…”
Section: Coiled‐coil‐rich Proteinsmentioning
confidence: 99%
“…B) from the rod‐shaped organism Corynebacterium glutamicum . RsmP is essential for viability, and its depletion leads to rounding up of the cells [Fiuza et al, ]. Consistent with its ability to polymerize spontaneously in vitro, RsmP assembles into massive, long filaments upon overproduction in C. glutamicum .…”
Section: Coiled‐coil‐rich Proteinsmentioning
confidence: 99%
“…DivIVA depletion leads to upregulation of RsmP, which has similarity to eukaryotic intermediate filaments [29]. RsmP is an essential protein and its homologs are unique to the Actinobacteria.…”
Section: Polar Growth Patterns In Specific Bacterial Taxamentioning
confidence: 99%